The Body Artist. An Experience of the Sur-Real in the Context of the Embodied and Aesthetic Abnormality - Kozin, Alexander (Qualitative Sociology Review, 2006)
In this essay I explore a possibility of experiential synthesis of an abnormal body of a Contergan person with an aesthetic image of the visual body. For a method, the essay uses phenomenology; I therefore lean in on the studies of embodiment conducted by Edmund Husserl and Maurice Merleau-Ponty. In turn, Max Ernst introduces an aesthetic modality of the artistic body. A personal narrative about meeting sur-real bodies serves as a frame for theorizing abnormality. The study reveals how the encounter with the abnormal ways of constitution suspends normality toward producing sur-real effects.